Green Finance Adoption: Unravelling The Behavioral Intention of Bank Employees in Batam Moderated By Internal Measures - Johny Budiman; Angelica Vivian Chrysti; Candy (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: Banks are adapting their strategies to align with environmental sustainability through green finance. In Indonesia, green finance is gaining attention, but challenges like inadequate employee attitudes have hindered its progress towards green finance. Purpose: This research aims to understand bank employee’s behavioral intentions as promoters in implementing green finance by examining the impact of attitude, self-efficacy, subjective norms, and behavior control based on the theory of planned behavior, as well as testing whether internal measures moderate the relationship between independent and dependent variables. Design/methodology/approach: This research uses a quantitative approach with a sample of 250 bank employees in Batam, Indonesia. Data were collected via Google Forms from October 16, 2023, to March 6, 2024, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings/Result: The study found that attitude, subjective norms, and behavioral control significantly impact bank employees' behavioral intentions in Batam City, while self-efficacy does not. Additionally, internal measures do not moderate the influence of attitude, self-efficacy, subjective norms, and perceived behavioral control on behavioral intention.Conclusion: This study explores how attitudes, self-efficacy, subjective norms, and perceived behavioral control influence bank employees' intentions to adopt green finance, moderated by internal measures, using the Theory of Planned Behavior. Understanding these factors can guide the banking sector in supporting the Sustainable Development Goals and achieving the 2030 Agenda.Originality/Value (State of The Art): While research on green finance in Indonesia’s banking sector is growing, studies on Batam City are limited. Given Batam's strategic economic role, understanding local banks' adoption of green finance is essential. This study explores the attitudes, behaviors, and challenges of bank employees in Batam, offering insights into the factors influencing green finance adoption in the region. Keywords: bank, behavioral intention, green finance, internal measures, theory of planned behavior